Liquid thermal conductive material, component assembly for producing thermal conductive sheet, thermal conductive

By using a high-thermal conductivity liquid thermal conductivity material and a layered structure of thermal conductivity in the thermal conductivity sheet, the problem of thermal resistance and flexibility of the thermal conductivity sheet in high-density semiconductor packages is solved, and more effective heat dissipation performance is achieved.

CN119137736APending Publication Date: 2024-12-13RESONAC CORP
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202380037698.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-07-22
Filing Date
2023-07-21
Publication Date
2024-12-13

AI Technical Summary

Technical Problem

When existing heat conductors cope with the increase in heat generation caused by the high performance and large-scale semiconductors, it is difficult to effectively reduce thermal resistance, especially when crimping between the heat generator and the heat dissipation body, the softness and low thermal resistance of the heat conductor are used. It's hard to take into account both sexes.

Method used

A liquid thermal conductivity material with a thermal conductivity of 5W/(m·K) or above is used, including thermally conductive fillers and resin components, and is coated on the thermally conductive layer to form a liquid layer. The liquid layer is used to flow and landfill the thermally conductive sheet and the thermally conductive sheet during heating and crimping. The gap of the adhesive body reduces contact thermal resistance, and optimizes thermal conductivity by adjusting the orientation of thermally conductive particles and the laminated structure.

Benefits of technology

It significantly reduces the thermal resistance of the heat conductor sheet, improves the flexibility and thermal conductivity of the heat conductor sheet, enhances the adhesion between the heat conductor sheet and the bonded body, and reduces contact thermal resistance. It is suitable for heat dissipation applications in high-density semiconductor packaging.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119137736A_ABST
    Figure CN119137736A_ABST
Patent Text Reader

Abstract

A liquid thermally conductive material having a thermal conductivity of 5 W / (mK) or more is used to form a liquid layer by being applied onto at least a portion of a thermally conductive layer containing thermally conductive particles.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present disclosure relates to a liquid heat-conducting material, a combination of components for making a heat-conducting sheet, a heat-conducting sheet, a heat-dissipating device and a method for making the heat-conducting sheet. Background Art

[0002] In recent years, the increased density of wiring and electronic components in semiconductor packages using multilayer wiring boards has increased heat generation, and the increased heat generation per unit area due to the high integration of semiconductor elements has increased, and it is desired to improve the heat dissipation from the semiconductor package.

[0003] Generally, a heat sink is used that dissipates heat by sandwiching thermal grease or a thermally conductive sheet between a heat generating body such as a semiconductor package and a heat sink such as aluminum or copper and making them close together. Generally, a thermally conductive sheet is more convenient in terms of workability when assembling a heat sink than thermally conductive grease.

[0004] In recent years, CPU (Central Processing Unit) chips have tended to be larger in area due to multi-core and multi-chip development. In addition, there is a tendency for the crimping pressure between the heat-generating CPU and the heat sink to decrease. Therefore, the thermal conductive sheet is required to be flexible during crimping. In addition, the thermal conductive sheet is required to have excellent thermal conductivity with low thermal resistance even if the thermal conductive sheet becomes thicker due to the height difference of the chip.

[0005] As a thermally conductive sheet, a resin sheet filled with a thermally conductive filler is also known. As a resin sheet with excellent thermal conductivity filled with a thermally conductive filler, a resin sheet in which highly thermally conductive inorganic particles are selected as the thermally conductive filler and the inorganic particles are oriented perpendicularly to the sheet surface has been proposed.

[0006] For example, there are proposed thermally conductive sheets in which a thermally conductive filler (boron nitride) is oriented in a direction substantially perpendicular to the sheet surface (see, for example, Patent Document 1), and thermally conductive sheets in which carbon fibers dispersed in a gel-like substance are oriented perpendicularly to the sheet surface (see, for example, Patent Document 2).

[0007] Prior art literature

[0008] Patent Literature

[0009] Patent Document 1: Japanese Patent Application Publication No. 2002-26202

[0010] Patent Document 2: Japanese Patent Application Publication No. 2001-250894 Summary of the invention

[0011] Technical problem to be solved by the invention

[0012] Patent Documents 1 and 2 study methods for orienting thermally conductive fillers, carbon fibers, etc. in a direction perpendicular to the sheet surface to suppress thermal resistance. In order to cope with the increase in heat generation associated with the high performance and large-scale semiconductors, it is desirable to further reduce the thermal resistance of thermally conductive sheets. Therefore, it is preferred to achieve low thermal resistance based on means other than the orientation of thermally conductive fillers, carbon fibers, etc. contained in the thermally conductive sheet.

[0013] The purpose of the present disclosure is to provide a liquid thermally conductive material that can reduce thermal resistance by being applied to a thermally conductive layer such as a thermally conductive sheet, a combination of components for making a thermally conductive sheet that has the aforementioned liquid thermally conductive material or a liquid thermally conductive material containing a metal component and can make a thermally conductive sheet with low thermal resistance, a thermally conductive sheet with low thermal resistance, a heat dissipation device having the thermally conductive sheet, and a method for making a thermally conductive sheet that can make a thermally conductive sheet with low thermal resistance.

[0014] Means for solving technical problems

[0015] Specific means for solving the above technical problems include the following.

[0016] <1> A liquid thermally conductive material having a thermal conductivity of 5 W / (m·K) or more, which is applied to at least a portion of a thermally conductive layer containing thermally conductive particles to form a liquid layer.

[0017] <2> The liquid thermally conductive material according to <1>, comprising a thermally conductive filler and a resin component.

[0018] <3> The liquid thermally conductive material according to <2>, wherein the thermally conductive filler has a particle size of 0.1 μm to 50 μm.

[0019] <4> The liquid thermally conductive material according to <2> or <3>, wherein the resin component includes a thermosetting resin component.

[0020] <5> The liquid thermally conductive material according to any one of <1> to <4>, which has a viscosity at 25° C. of 4000 Pa·s or less.

[0021] <6> A combination of components for producing a thermally conductive sheet, comprising the liquid thermally conductive material according to any one of <1> to <5>, and a thermally conductive material containing thermally conductive particles.

[0022] <7> A combination of components for producing a thermally conductive sheet, comprising a liquid thermally conductive material containing a metal component and a thermally conductive material containing thermally conductive particles.

[0023] <8> The combination of components for producing a thermally conductive sheet according to <7>, wherein the melting point of the metal component is 50° C. or less.

[0024] <9> A thermally conductive sheet comprising:

[0025] a heat-conductive layer comprising a heat-conductive material including heat-conductive particles; and

[0026] A liquid layer, the liquid layer is located on at least a portion of the main surface of the above-mentioned thermally conductive layer and contains a first liquid thermally conductive material or a second liquid thermally conductive material, the first liquid thermally conductive material is any one of <1> to <5>, and the second liquid thermally conductive material is a liquid thermally conductive material containing a metal component.

[0027] <10> The thermally conductive sheet according to <9>, wherein the thermally conductive particles include at least one type of graphite particles (A) selected from the group consisting of flaky particles, ellipsoidal particles, and rod-shaped particles,

[0028] For the above-mentioned heat-conductive layer, in the case of the above-mentioned scaly particles, the surface direction is oriented along the thickness direction of the above-mentioned heat-conductive layer, in the case of the above-mentioned ellipsoidal particles, the major axis direction is oriented along the thickness direction of the above-mentioned heat-conductive layer, and in the case of the above-mentioned rod-shaped particles, the major axis direction is oriented along the thickness direction of the above-mentioned heat-conductive layer.

[0029] <11> The thermally conductive sheet according to <9> or <10>, wherein the maximum thickness of the liquid layer is 0.5 μm to 20 μm.

[0030] <12> The thermally conductive sheet according to any one of <9> to <11>, wherein the liquid layer includes the first liquid thermally conductive material, and the liquid layer can be cured by heating.

[0031] <13> A heat dissipation device comprising a heat generating element, a heat dissipating element, and a thermally conductive sheet according to any one of <9> to <11> disposed between the heat generating element and the heat dissipating element,

[0032] The liquid layer is located on at least a portion of at least one of the main surface of the heat conductive layer located on the heating element side and the main surface of the heat conductive layer located on the heat radiating element side.

[0033] <14> A heat dissipation device comprising a heating element, a heat dissipation element, and a heat conductive sheet, wherein the heat conductive sheet is arranged between the heating element and the heat dissipation element and is the heat conductive sheet described in <12>, and the heat conductive sheet comprises an adhesive layer formed by solidifying the liquid layer.

[0034] The adhesive layer is located on at least a portion of at least one of the main surface of the heat conductive layer located on the heating element side and the main surface of the heat conductive layer located on the heat dissipating element side.

[0035] <15> A method for producing a thermally conductive sheet, the method comprising producing the thermally conductive sheet according to any one of <9> to <12>,

[0036] The manufacturing method of the thermal conductive sheet comprises:

[0037] A step of preparing a composition containing the thermally conductive particles;

[0038] A process of forming the thermal conductive layer using the composition; and

[0039] A step of forming a liquid layer on at least a portion of the main surface of the heat conductive layer.

[0040] <16> A method for manufacturing a thermally conductive sheet, which is a method for manufacturing the thermally conductive sheet described in <10>,

[0041] The manufacturing method of the thermal conductive sheet comprises:

[0042] A step of preparing a composition containing the graphite particles (A);

[0043] A step of forming the composition into a sheet to obtain a sheet;

[0044] A step of manufacturing a laminate of the above-mentioned sheets;

[0045] a step of slicing the side end surface of the laminate; and

[0046] A step of forming a liquid layer on at least a portion of the main surface of the sliced ​​sheet corresponding to the heat conductive layer obtained by slicing.

[0047] Effects of the Invention

[0048] According to the present disclosure, there can be provided a liquid thermally conductive material that can reduce thermal resistance by being applied to a thermally conductive layer of a thermally conductive sheet, etc., a combination of components for making a thermally conductive sheet that has the aforementioned liquid thermally conductive material or a liquid thermally conductive material containing a metal component and can produce a thermally conductive sheet with low thermal resistance, a thermally conductive sheet with low thermal resistance, a heat dissipation device having the thermally conductive sheet, and a method for manufacturing a thermally conductive sheet that can produce a thermally conductive sheet with low thermal resistance. BRIEF DESCRIPTION OF THE DRAWINGS

[0049] Figure 1 This is a schematic structural diagram of a thermally conductive sheet according to one embodiment of the present invention.

[0050] Figure 2 This is a schematic cross-sectional view of a heat dissipation device in which a heat generating element is a semiconductor chip and a heat dissipating element is a heat sink according to an embodiment of the present invention.

[0051] Figure 3 The diagrams show the states of interfaces obtained by image analysis in Examples 1 to 4 and Comparative Examples 1 and 2. DETAILED DESCRIPTION

[0052] The following is a detailed description of the embodiments for implementing the present invention. However, the present invention is not limited to the following embodiments. In the following embodiments, unless otherwise specified, the constituent elements (including element steps, etc.) are not essential. The numerical values ​​and their ranges are also the same and do not limit the present invention.

[0053] The term "process" used in the present disclosure includes not only a process that is independent of other processes, but also a process that cannot be clearly distinguished from other processes as long as the purpose of the process can be achieved.

[0054] In the present disclosure, in a numerical range expressed by “to”, the numerical values ​​before and after “to” are included as the minimum value and the maximum value, respectively.

[0055] In the numerical range recorded in the present disclosure, the upper limit or lower limit recorded in one numerical range can be replaced by the upper limit or lower limit of the numerical range recorded in other segments. In addition, in the numerical range recorded in the present disclosure, the upper limit or lower limit of the numerical range can also be replaced by the value shown in the embodiment.

[0056] In the present disclosure, each component may include a plurality of substances corresponding thereto. When a plurality of substances corresponding to each component are present in the composition, the content rate or content of each component refers to the total content rate or content of the plurality of substances present in the composition unless otherwise specified.

[0057] In the present disclosure, particles corresponding to each component may contain multiple types. When multiple types of particles corresponding to each component exist in the composition, the particle size of each component refers to the value of the mixture of the multiple types of particles present in the composition unless otherwise specified.

[0058] The term “layer” or “film” used in the present disclosure includes not only a case where the layer or film is formed throughout the entire region when the region where the layer or film exists is observed, but also a case where the layer or film is formed only in a part of the region.

[0059] The term "stacked" in the present disclosure means overlapping layers, and two or more layers may be combined together, or two or more layers may be detachable.

[0060] 〔Liquid thermal conductive material〕

[0061] The liquid thermally conductive material disclosed herein has a thermal conductivity of 5 W / (m·K) or more and is a material to be applied to at least a portion of a thermally conductive layer including thermally conductive particles to form a liquid layer.

[0062] In the present disclosure, the liquid thermally conductive material refers to a thermally conductive material that is liquid at at least a portion of the temperature between 0°C and 50°C.

[0063] In the present disclosure, thermal conductivity can be measured by a xenon flash (Xe-flash) method.

[0064] The resistance (also called "contact thermal resistance") caused by the gap generated by the contact between the thermally conductive sheet and the adherends such as the heat generating body and the heat sink in contact with the thermally conductive sheet is difficult to reduce by the structure of the thermally conductive particles contained in the thermally conductive sheet or the composition of the thermally conductive sheet. The liquid thermally conductive material disclosed herein is a material used to form a thermally conductive sheet having a liquid layer by coating at least a portion of a thermally conductive layer containing thermally conductive particles. When the thermally conductive layer formed with the liquid layer is heated and pressure-bonded to the adherends such as the heat generating body and the heat sink, the liquid layer flows between the thermally conductive layer and the adherend. As a result, the gap between the thermally conductive sheet and the adherend (for example, the gap caused by the unevenness of the thermally conductive sheet) is filled with the flowing liquid layer, so that the thermally conductive sheet and the adherend can be tightly fitted with the help of the liquid layer. As a result, the contact thermal resistance is greatly reduced. Furthermore, by setting the thermal conductivity of the liquid thermally conductive material to 5 W / (m·K) or more, it is possible to suppress a decrease in the thermal conductivity of the thermally conductive sheet due to the liquid layer being disposed on the thermally conductive layer, thereby suppressing an increase in the thermal resistance of the thermally conductive sheet.

[0065] Contact thermal resistance is also likely to occur when there are irregularities on the surface of an adherend such as a heating element or a heat sink. In this case, it is difficult to reduce the thermal resistance by adjusting the orientation of the thermally conductive filler contained in the thermally conductive sheet. On the other hand, by using the liquid thermally conductive material disclosed herein, the thermally conductive sheet and the adherend with irregularities on the surface can be closely fitted with the aid of a liquid layer. At this time, the gaps generated when the thermally conductive sheet and the adherend are heated and pressed together (for example, the gaps caused by the irregularities on the adherend) are filled with the liquid layer, so the contact thermal resistance is greatly reduced.

[0066] The liquid thermally conductive material of the present disclosure preferably includes a thermally conductive filler and a resin component. The resin component may include a component that is liquid at 25°C.

[0067] Examples of the thermally conductive filler include metal-containing particles and non-metallic particles having excellent thermal conductivity. The thermally conductive filler may have a thermal conductivity of 10 W / (m·K) or more. The thermally conductive filler may be insulating or conductive.

[0068] The thermally conductive filler may be particles of at least one selected from the group consisting of silver, aluminum oxide, aluminum hydroxide, magnesium oxide, beryllium oxide, boron nitride, aluminum nitride, silicon nitride, silicon carbide, silicon dioxide, aluminum fluoride, calcium fluoride, zinc oxide, diamond, gallium, indium, and tin.

[0069] The thermally conductive filler contained in the liquid thermally conductive material may be a single type or a combination of two or more types.

[0070] The liquid thermally conductive material disclosed herein may or may not contain low-melting-point metal particles having a melting point of 200° C. or less.

[0071] From the viewpoint of excellent thermal conductivity and further reducing the gap between the adherend and the thermally conductive sheet, the particle size of the thermally conductive filler may be 0.1 μm to 50 μm, 0.2 μm to 20 μm, or 0.5 μm to 10 μm.

[0072] The particle size (D50) of the thermally conductive filler is measured using a laser diffraction particle size distribution device (e.g., "Microtrac Series MT3300" manufactured by Nikkiso Co., Ltd.) using a laser diffraction / scattering method, and corresponds to the particle size at which the mass accumulation reaches 50% when a mass cumulative particle size distribution curve is plotted from the smaller particle size side.

[0073] The resin component may be a non-curable resin component or a curable resin component such as a thermosetting resin component or a photocurable resin component. From the viewpoint of adhesion to an adherend, thermal conductivity, etc. during curing, the resin component preferably includes a thermosetting resin component. The resin component may contain one resin component or may contain two or more resin components.

[0074] As the non-curable resin component, a non-curable resin component that is liquid at 25° C. is preferred, and a liquid silicone compound, a liquid (meth)acrylic compound, a liquid polyester compound, and the like are more preferred.

[0075] As the thermosetting resin component, a thermosetting resin component which is liquid at 25° C. is preferred, and a liquid epoxy compound, a curable liquid silicone compound, a curable liquid (meth)acrylic compound, and the like are more preferred.

[0076] For example, from the viewpoint of the balance between thermal conductivity and adhesion, the content of the thermally conductive filler contained in the liquid thermally conductive material is preferably 70% to 98% by mass, more preferably 75% to 95% by mass, and even more preferably 80% to 93% by mass, relative to the total amount of the liquid thermally conductive material.

[0077] From the perspective of the balance between thermal conductivity and adhesion, for example, the content of the resin component in the liquid thermally conductive material is preferably 2% to 30% by mass, more preferably 5% to 25% by mass, and even more preferably 7% to 20% by mass, relative to the total amount of the liquid thermally conductive material.

[0078] The total content of the thermally conductive filler and the resin component contained in the liquid thermally conductive material may be 80% by mass to 100% by mass, or 90% by mass to 100% by mass, based on the total amount of the liquid thermally conductive material.

[0079] The liquid thermally conductive material may or may not contain components other than the thermally conductive filler and the resin component.

[0080] The viscosity of the liquid thermally conductive material disclosed herein at 25° C. is preferably 4000 Pa·s or less, and may be 0.001 Pa·s to 3000 Pa·s, or 10 Pa·s to 2000 Pa·s. By setting the viscosity at 25° C. to 4000 Pa·s or less, the liquid layer easily flows between the thermally conductive layer and the adherend, and thus the gap between the thermally conductive sheet and the adherend tends to be properly filled by the liquid layer.

[0081] The viscosity at 25°C was measured using a rheometer at 5.0 s at 25°C. -1 Specifically, the viscosity is the shear viscosity measured at a temperature of 25° C. using a rotary shear viscometer equipped with a cone plate (diameter 40 mm, cone angle 0°).

[0082] [Combination of components for manufacturing a thermal conductive sheet 1]

[0083] The combination 1 of components for making a thermally conductive sheet disclosed in the present invention comprises the liquid thermally conductive material disclosed in the present invention and a thermally conductive material containing thermally conductive particles. The thermally conductive material is a material for forming a thermally conductive layer of the thermally conductive sheet. The thermally conductive sheet can be obtained by coating the liquid thermally conductive material on at least a portion of the thermally conductive layer composed of the thermally conductive material to form a liquid layer.

[0084] The thermally conductive material preferably contains thermally conductive particles and is solid at 25°C.

[0085] The thermally conductive material includes thermally conductive particles. The thermally conductive particles are preferably at least one selected from graphite, carbon, silver, aluminum oxide, aluminum hydroxide, magnesium oxide, beryllium oxide, boron nitride, aluminum nitride, silicon nitride, silicon carbide, silicon dioxide, aluminum fluoride, calcium fluoride, and zinc oxide. From the viewpoint of thermal conductivity when used as a thermally conductive layer, the thermally conductive particles are preferably graphite particles, carbon particles, and boron nitride particles, and more preferably graphite particles.

[0086] The thermally conductive particles are preferably at least one selected from the group consisting of flaky particles, ellipsoidal particles, and rod-shaped particles, and more preferably at least one graphite particle selected from the group consisting of flaky particles, ellipsoidal particles, and rod-shaped particles (hereinafter also referred to as "graphite particles (A)"). Preferably, in the case of flaky particles, the surface direction of the thermally conductive particles is oriented along the thickness direction of the thermally conductive material, preferably, in the case of ellipsoidal particles, the major axis direction of the thermally conductive particles is oriented along the thickness direction of the thermally conductive material, and preferably, in the case of rod-shaped particles, the major axis direction of the thermally conductive particles is oriented along the thickness direction of the thermally conductive material.

[0087] Hereinafter, a preferred embodiment in which the thermally conductive particles are graphite particles (A) will be described.

[0088] Preferably, the graphite particles (A) are oriented in the thickness direction of the thermal conductive material in the case of flaky particles, in the thickness direction of the thermal conductive material in the case of ellipsoidal particles, and in the thickness direction of the thermal conductive material in the case of rod-shaped particles. In addition, it is more preferred that the six-membered ring plane in the graphite particle (A) crystal is oriented in the face direction in the case of flaky particles, in the long axis direction in the case of ellipsoidal particles, and in the long axis direction in the case of rod-shaped particles. The six-membered ring plane refers to the plane in which the six-membered ring is formed in the hexagonal crystal system, that is, the (0001) crystal plane.

[0089] The shape of the graphite particles (A) is more preferably flaky. By selecting flaky graphite particles, there is a tendency for the thermal conductivity to be further improved. This is believed to be because, for example, flaky graphite particles are more easily oriented in a predetermined direction in the thermal conductive material.

[0090] Whether the six-membered ring planes in the crystal of the graphite particle (A) are oriented along the plane direction of the flaky particles, the long axis direction of the ellipsoidal particles, or the long axis direction of the rod-shaped particles can be confirmed by X-ray diffraction measurement. Specifically, the orientation direction of the six-membered ring planes in the crystal of the graphite particle (A) is confirmed by the following method.

[0091] First, a sample sheet for measurement is prepared in which the plane direction of the flaky particles of the graphite particles (A), the major axis direction of the ellipsoidal particles, or the major axis direction of the rod-shaped particles are oriented along the plane direction of the sheet. Specific methods for preparing the sample sheet for measurement include, for example, the following methods.

[0092] A mixture of a resin and graphite particles (A) in an amount of 10% by volume or more relative to the resin is formed into a sheet. The "resin" used is not particularly limited as long as it is a material that does not show a peak that hinders X-ray diffraction and can be formed into a sheet. Specifically, an amorphous resin having cohesive force as a binder such as acrylic rubber, NBR (acrylonitrile butadiene rubber), and SIBS (styrene-isobutylene-styrene copolymer) can be used.

[0093] The sheet of the mixture is pressed to less than 1 / 10 of the original thickness, and a plurality of the pressed sheets are stacked to form a laminate. The operation of further pressing the laminate to less than 1 / 10 is repeated more than 3 times to obtain a sample sheet for measurement. By this operation, in the sample sheet for measurement, the graphite particles (A) are oriented in the plane direction along the plane direction of the sample sheet for measurement in the case of flaky particles, in the case of ellipsoidal particles, in the state of being oriented in the plane direction of the sample sheet for measurement, and in the case of rod-shaped particles, in the state of being oriented in the plane direction of the sample sheet for measurement.

[0094] The surface of the sample sheet for measurement prepared as described above was subjected to X-ray diffraction measurement. The height H1 of the peak corresponding to the (110) plane of graphite appearing near 2θ = 77° and the height H2 of the peak corresponding to the (002) plane of graphite appearing near 2θ = 27° were measured. The value obtained by dividing H1 by H2 of the sample sheet for measurement prepared in this way was 0 to 0.02.

[0095] Therefore, "the hexagonal ring planes in the crystals of the graphite particles (A) are oriented in the plane direction in the case of flaky particles, in the major axis direction in the case of ellipsoidal particles, and in the major axis direction in the case of rod-shaped particles" means that the surface of a sheet containing graphite particles (A) is measured by X-ray diffraction, and the value obtained by dividing the height of the peak corresponding to the (110) plane of the graphite particles (A) appearing near 2θ=77° by the height of the peak corresponding to the (002) plane of the graphite particles (A) appearing near 2θ=27° is 0 to 0.02.

[0096] In the present disclosure, X-ray diffraction measurement is performed under the following conditions.

[0097] Device: For example, Burker AXS Corporation "D8DISCOVER"

[0098] X-ray source: CuKα with a wavelength of 1.5406nm, 40kV, 40mA

[0099] Step length (measurement of stride width): 0.01°

[0100] Step time: 720 seconds

[0101] Among them, "graphite particles are oriented along the thickness direction of the thermal conductive material in the case of flaky particles, along the thickness direction of the thermal conductive material in the case of ellipsoidal particles, and along the thickness direction of the thermal conductive material in the case of rod-shaped particles" means that the angle formed by the surface direction and the surface (main surface) of the thermal conductive material (hereinafter also referred to as "orientation angle") is 60° or more in the case of flaky particles, the angle formed by the long axis direction and the surface (main surface) of the thermal conductive material (hereinafter also referred to as "orientation angle") is 60° or more in the case of ellipsoidal particles, and the angle formed by the long axis direction and the surface (main surface) of the thermal conductive material (hereinafter also referred to as "orientation angle") is 60° or more in the case of rod-shaped particles. The orientation angle is preferably 80° or more, more preferably 85° or more, and further preferably 88° or more.

[0102] The orientation angle is an average value obtained by observing a cross section of a thermal conductive material using a SEM (scanning electron microscope) and measuring the angles (orientation angles) formed by the plane direction in the case of flaky particles, the major axis direction in the case of ellipsoidal particles, and the major axis direction in the case of rod-shaped particles and the surface (main surface) of the thermal conductive material for any 50 graphite particles (A).

[0103] The particle size of the graphite particles (A) is not particularly limited. The average particle size of the graphite particles (A) is preferably more than 1 / 2 of the average thickness of the thermally conductive material and less than the average thickness in terms of the mass average particle size. If the mass average particle size of the graphite particles (A) is more than 1 / 2 of the average thickness of the thermally conductive material, an effective heat conduction path can be formed in the thermally conductive material, and there is a tendency for the thermal conductivity to be improved. If the mass average particle size of the graphite particles (A) is less than the average thickness of the thermally conductive material, it is possible to suppress the graphite particles (A) from protruding from the surface of the thermally conductive material, and there is a tendency for the surface of the thermally conductive material to have excellent adhesion.

[0104] There is no particular limitation on the method for preparing the thermal conductive material in a manner that the plane direction in the case of flaky particles, the major axis in the case of ellipsoidal particles, and the major axis direction in the case of rod-shaped particles are oriented in the thickness direction, and for example, the method described in Japanese Patent Publication No. 2008-280496 can be used. Specifically, the following method can be used: a sheet is prepared using a composition, the sheets are stacked to prepare a laminate, and the side end face of the laminate (for example, at an angle of 0° to 30° relative to the normal line from the main surface of the laminate) is sliced ​​(hereinafter also referred to as "laminated slicing method").

[0105] In addition, when the above-mentioned stacking and slicing method is used, the particle size of the graphite particles (A) used as the raw material is preferably more than 1 / 2 times the average thickness of the thermal conductive material in terms of mass average particle size, and may also exceed the average thickness. The reason why the particle size of the graphite particles (A) used as the raw material may also exceed the average thickness of the thermal conductive material is that, for example, even if graphite particles (A) having a particle size exceeding the average thickness of the thermal conductive material are contained, since the thermal conductive material is formed by slicing together with the graphite particles (A), the graphite particles (A) will not protrude from the surface of the thermal conductive material. In addition, when slicing together with the graphite particles (A), a large number of graphite particles (A) that penetrate the thickness direction of the thermal conductive material are generated, which can form an extremely effective thermal conductive path, and has a tendency to further improve thermal conductivity.

[0106] When the stacking section method is used, the particle size of the graphite particles (A) used as the raw material is more preferably 1 to 5 times the average thickness of the thermally conductive material in terms of mass average particle size, and more preferably 2 to 4 times. If the mass average particle size of the graphite particles (A) is more than 1 times the average thickness of the thermally conductive material, an effective heat conduction path can be further formed, and the thermal conductivity is further improved. If it is less than 5 times the average thickness of the thermally conductive material, the area occupied by the graphite particles (A) on the surface portion can be suppressed from becoming too large, and the reduction of adhesion can be suppressed.

[0107] The mass average particle size (D50) of the graphite particles (A) is measured using a laser diffraction particle size distribution device (e.g., Microtrac Series MT3300, manufactured by Nikkiso Co., Ltd.) using a laser diffraction / scattering method, and corresponds to a particle size at which the mass accumulation reaches 50% when a mass cumulative particle size distribution curve is plotted from the smaller particle size side.

[0108] The thermal conductive material may contain graphite particles other than flaky particles, ellipsoidal particles and rod-shaped particles, and may contain spherical graphite particles, artificial graphite particles, exfoliated graphite particles, acid-treated graphite particles, expanded graphite particles, carbon fibers and the like.

[0109] The graphite particles (A) are preferably flaky particles, and flaky expanded graphite particles obtained by pulverizing flaky expanded graphite are preferred because flaky particles having high crystallinity and large particle size can be easily obtained.

[0110] For example, from the viewpoint of the balance between thermal conductivity and adhesion, the content of the graphite particles (A) in the thermal conductive material is preferably 15 to 50% by volume, more preferably 20 to 45% by volume, and even more preferably 25 to 40% by volume.

[0111] When the content of the graphite particles (A) is 15% by volume or more, thermal conductivity tends to be improved, while when the content of the graphite particles (A) is 50% by volume or less, reduction in pressure-sensitive adhesiveness and adhesion tends to be suppressed.

[0112] Furthermore, when the thermal conductive material contains graphite particles other than flaky particles, ellipsoidal particles, and rod-shaped particles, the content of the entire graphite particles is preferably within the above range.

[0113] The content (volume %) of the graphite particles (A) is a value obtained by the following formula.

[0114] Content of graphite particles (A) (volume %) = [(Aw / Ad) / {(Aw / Ad)+(Xw / Xd)}]×100

[0115] Aw: mass composition of graphite particles (A) (mass %)

[0116] Xw: Mass composition of other optional components (mass %)

[0117] Ad: Density of graphite particles (A) (Calculated with Ad being 2.1 in this disclosure)

[0118] Xd: Density of any other component

[0119] The content of the spherical graphite particles, artificial graphite particles, acid-treated graphite particles or carbon fibers in the thermal conductive layer may be independently 0% to 10% by volume, 0% to 5% by volume, or 0% to 1% by volume.

[0120] The mass ratio of graphite particles (A) to carbon fibers in the thermally conductive layer, i.e., graphite particles (A): carbon fibers, may be 100:0 to 100:30, 100:0 to 100:20, or 100:0 to 100:10. Carbon fibers are generally hard, and by making the amount of carbon fibers smaller than that of graphite particles (A), the flexibility of the thermally conductive sheet can be ensured, and an increase in contact thermal resistance tends to be suppressed.

[0121] <Ingredient (B) that is liquid at 25°C>

[0122] The thermal conductive material may contain a component that is liquid at 25°C (hereinafter also referred to as "liquid component (B)"). In the present disclosure, "liquid at 25°C" means a substance that exhibits fluidity and viscosity at 25°C, and the viscosity, which is a measure of viscosity, is 0.0001 Pa·s to 1000 Pa·s at 25°C. The viscosity of the component that is liquid at 25°C is measured using a rheometer at 5.0s at 25°C. -1Specifically, the "viscosity" is the shear viscosity measured at a temperature of 25°C using a rotational shear viscometer equipped with a cone plate (diameter 40 mm, cone angle 0°).

[0123] The viscosity of the liquid component (B) at 25°C is preferably 0.001 Pa·s to 100 Pa·s, more preferably 0.01 Pa·s to 10 Pa·s.

[0124] The liquid component (B) is not particularly limited as long as it is liquid at 25°C, and is preferably a high molecular compound (polymer). Examples of the liquid component (B) include polybutene, polyisoprene, polysulfide, acrylonitrile rubber, silicone rubber, hydrocarbon resin, terpene resin, acrylic resin, etc. Among them, from the viewpoint of heat resistance, the liquid component (B) preferably contains polybutene. The liquid component (B) may be used alone or in combination of two or more.

[0125] Among them, polybutene refers to a polymer obtained by polymerizing isobutylene or normal butene. It also includes a polymer obtained by copolymerizing isobutylene and normal butene. Structurally, it refers to a polymer having a structural unit represented by "-CH2-C(CH3)2-" or "-CH2-CH(CH2CH3)-". It is sometimes also called polyisobutylene. As long as polybutene contains the above structure, there is no particular limitation on other structures.

[0126] Examples of polybutene include homopolymers of butene and copolymers of butene and other monomer components. Examples of copolymers with other monomer components include copolymers of isobutylene and styrene or copolymers of isobutylene and ethylene. The copolymer may be any of a random copolymer, a block copolymer, and a graft copolymer.

[0127] Examples of polybutene include "NOF Polybutene" produced by NOF Corporation. TM EMAWET (registered trademark)”, “Nisseki Polybutene” of JXTG Nippon Oil & Energy Corporation, “Tetrax” of JXTG Nippon Oil & Energy Corporation, “Himol” of JXTG Nippon Oil & Energy Corporation, and “Polyisobutylene” of Tomoe Industries Co., Ltd.

[0128] It is believed that the liquid component (B) mainly functions as a stress relaxant and a pressure-sensitive adhesive agent having excellent heat resistance and humidity resistance. In addition, the cohesive force and fluidity during heating tend to be further improved by using the hot melt agent (E) described later.

[0129] From the viewpoint of further improving pressure-sensitive adhesive force, adhesion, sheet strength, hydrolysis resistance, etc., the content of the liquid component (B) in the thermally conductive material is preferably 10% to 55% by volume, more preferably 15% to 50% by volume, and even more preferably 20% to 50% by volume.

[0130] When the content of the liquid component (B) is 10% by volume or more, the pressure-sensitive adhesiveness and adhesion tend to be further improved. When the content of the liquid component (B) is 55% by volume or less, the decrease in sheet strength and thermal conductivity tends to be more effectively suppressed.

[0131] <Acrylate polymer (C)>

[0132] The heat conductive material may contain an acrylate polymer (C). It is considered that the acrylate polymer (C) mainly functions as a pressure-sensitive adhesive agent and an elasticity-imparting agent for restoring the thickness in accordance with the warping.

[0133] As the acrylic ester polymer (C), for example, it is preferable to use an acrylic ester polymer (so-called acrylic rubber) obtained by copolymerizing butyl acrylate, ethyl acrylate, acrylonitrile, acrylic acid, glycidyl methacrylate, 2-vinylhexyl acrylate, etc. as main raw material components and methyl acrylate, etc. as needed. The acrylic ester polymer (C) may be used alone or in combination of two or more.

[0134] The weight average molecular weight of the acrylic polymer (C) is preferably 100,000 to 1,000,000, more preferably 250,000 to 700,000, and even more preferably 400,000 to 600,000. A weight average molecular weight of 100,000 or more tends to provide excellent film strength, while a weight average molecular weight of 1,000,000 or less tends to provide excellent flexibility.

[0135] The weight average molecular weight is determined by gel permeation chromatography using a calibration curve of standard polystyrene.

[0136] The glass transition temperature (Tg) of the acrylic polymer (C) is preferably 20° C. or lower, more preferably -70° C. to 0° C., and further preferably -50° C. to -20° C. When the glass transition temperature is 20° C. or lower, the acrylate polymer (C) tends to have excellent flexibility and pressure-sensitive adhesiveness.

[0137] The glass transition temperature (Tg) can be calculated by performing dynamic viscoelasticity measurement by stretching and tan δ derived from the measurement.

[0138] The acrylate polymer (C) may be present in the entire thermal conductive material by internal addition, or may be locally present on the surface by surface coating or impregnation. In particular, coating or impregnation on one side is preferred because strong adhesion can be imparted only to one side, which is preferred from the perspective of obtaining a sheet with good workability.

[0139] The content of the acrylic ester polymer (C) in the heat conductive layer is preferably 3% by volume to 25% by volume, more preferably 5% by volume to 20% by volume, and even more preferably 7% by volume to 15% by volume.

[0140] <Hot melt (D)>

[0141] The heat conductive material may further contain a hot melt (D). The hot melt (D) has the effect of increasing the strength of the heat conductive material and improving the fluidity when heated.

[0142] Examples of the hot melt agent (D) include aromatic petroleum resins, terpene phenolic resins, and cyclopentadiene petroleum resins. In addition, the hot melt agent (D) may be a hydrogenated aromatic petroleum resin or a hydrogenated terpene phenolic resin. The hot melt agent (D) may be used alone or in combination of two or more.

[0143] Among them, when polybutene is used as the liquid component (B), the hot melt (D) preferably contains at least one selected from hydrogenated aromatic petroleum resins and hydrogenated terpene phenolic resins. These hot melts (D) have high stability and excellent compatibility with polybutene, and therefore, when constituting a thermally conductive material, there is a tendency to achieve better thermal conductivity, flexibility, and workability.

[0144] Examples of commercially available hydrogenated aromatic petroleum resins include "Arkon" from Arakawa Chemical Industries, Ltd. and "i-marv" from Idemitsu Kosan Co., Ltd. In addition, examples of commercially available hydrogenated terpene phenolic resins include "CLEARON" from Yasuhara Chemical Co., Ltd. In addition, examples of commercially available cyclopentadiene petroleum resins include "Quintone" from Japan Zeon Corporation and "MARUKA LYNCUR" from Maruzen Petrochemical Co., Ltd.

[0145] The hot melt (D) is solid at 25°C, and preferably has a softening temperature of 40°C to 150°C. If a thermoplastic resin is used as the hot melt (D), the softening fluidity during thermocompression bonding is improved, resulting in a tendency to improve adhesion. In addition, if the softening temperature is above 40°C, the cohesive force near room temperature can be maintained, resulting in a tendency to easily obtain the required sheet strength and excellent handling properties. If the softening temperature is below 150°C, the softening fluidity during thermocompression bonding becomes high, resulting in a tendency to improve adhesion. The softening temperature is more preferably 60°C to 120°C. In addition, the softening temperature is measured by the ring and ball method (JIS K2207: 1996).

[0146] From the viewpoint of improving pressure-sensitive adhesive force, adhesion, sheet strength, etc., the content of the hot melt (D) in the thermally conductive material is preferably 3 to 25 volume %, more preferably 5 to 20 volume %, and even more preferably 5 to 15 volume %.

[0147] When the content of the hot melt agent (D) is 3% by volume or more, pressure-sensitive adhesive strength, heating fluidity, sheet strength, etc. tend to be sufficient, and when it is 25% by volume or less, flexibility tends to be sufficient, resulting in excellent handleability and heat cycle resistance.

[0148] <Antioxidant (E)>

[0149] The thermal conductive material may also contain an antioxidant (F) for the purpose of imparting thermal stability at high temperatures. As the antioxidant (E), phenolic antioxidants, phosphorus antioxidants, amine antioxidants, sulfur antioxidants, hydrazine antioxidants, amide antioxidants, etc. can be listed. The antioxidant (E) can be appropriately selected according to the temperature conditions used, and is more preferably a phenolic antioxidant. One antioxidant (E) can be used alone, or two or more can be used in combination.

[0150] Examples of commercially available phenolic antioxidants include ADK STAB AO-50, ADK STAB AO-60, and ADK STAB AO-80 from ADEKA Corporation.

[0151] The content of the antioxidant (E) in the thermal conductive material is not particularly limited, but is preferably 0.1% to 5% by volume, more preferably 0.2% to 3% by volume, and further preferably 0.3% to 1% by volume. If the content of the antioxidant (E) is 0.1% by volume or more, there is a tendency to obtain a sufficient antioxidant effect. If the content of the antioxidant (E) is 5% by volume or less, there is a tendency to suppress the reduction in the strength of the thermal conductive material.

[0152] <Other ingredients>

[0153] According to the purpose, the thermal conductive material may also contain other components except graphite particles (A), liquid components (B), acrylate polymers (C), hot melts (D), and antioxidants (E). For example, from the viewpoint of flame retardancy, the thermal conductive material may also contain a flame retardant. The flame retardant is not particularly limited and can be appropriately selected from commonly used flame retardants. For example, red phosphorus flame retardants and phosphate flame retardants can be listed. Among them, from the viewpoint of excellent safety and improving adhesion by plasticizing effect, phosphate flame retardants are preferred.

[0154] As the red phosphorus flame retardant, in addition to using simple red phosphorus particles, various coated red phosphorus flame retardants, masterbatch red phosphorus flame retardants, etc. can also be used for the purpose of improving safety or stability. Specifically, Nobaredo, Nobaclexel, Nobacle, Nobaperet (all trade names) of Phosphorus Chemical Industry Co., Ltd. can be cited.

[0155] As phosphate flame retardants, there can be listed aliphatic phosphates such as trimethyl phosphate, triethyl phosphate, and tributyl phosphate; aromatic phosphates such as triphenyl phosphate, tricresyl phosphate, cresyl diphenyl phosphate, tricresyl phosphate, cresyl di(2,6-xylyl) phosphate, tri(t-butylated phenyl) phosphate, tri(isopropylated phenyl) phosphate, and isopropylated products of triaryl phosphates; aromatic condensed phosphates such as resorcinol bisdiphenyl phosphate, bisphenol A bis(diphenyl phosphate), and resorcinol bis[di(dimethylphenyl) phosphate]; and the like.

[0156] Among them, bisphenol A bis(diphenyl phosphate) is preferred from the viewpoint of being excellent in hydrolysis resistance and having an excellent effect of improving adhesion due to a plasticizing effect.

[0157] The content of the flame retardant in the thermally conductive material is not particularly limited and can be used in an amount that can exert flame retardancy, preferably set to about 30 volume % or less. From the viewpoint of suppressing the deterioration of thermal resistance caused by the leakage of the flame retardant component to the surface of the thermally conductive layer, it is preferably set to 20 volume % or less.

[0158] [Combination of components for manufacturing a thermal conductive sheet 2]

[0159] The combination 2 of components for making a thermally conductive sheet disclosed herein comprises a liquid thermally conductive material containing a metal component and a thermally conductive material containing thermally conductive particles. The thermally conductive sheet can be obtained by coating the liquid thermally conductive material containing a metal component on at least a portion of a thermally conductive layer composed of a thermally conductive material to form a liquid layer.

[0160] The preferred embodiment of the thermally conductive material in the combination 2 of components for making a thermally conductive sheet disclosed herein is the same as the preferred embodiment of the thermally conductive material in the combination 1 of components for making a thermally conductive sheet disclosed herein.

[0161] The combination 2 of parts for making a thermally conductive sheet disclosed in the present invention is a material for forming a thermally conductive sheet having a liquid layer by coating a liquid thermally conductive material containing a metal component on at least a portion of a thermally conductive layer formed of a thermally conductive material. When the thermally conductive layer formed with the liquid layer is heated and pressed against an adherend such as a heating element or a heat sink, the liquid layer flows between the thermally conductive layer and the adherend. As a result, the gap between the thermally conductive sheet and the adherend is filled with the flowing liquid layer, so that the thermally conductive sheet and the adherend can be closely fitted with the aid of the liquid layer. As a result, the contact thermal resistance is greatly reduced. Furthermore, by including a metal component in the liquid layer, the thermal conductivity of the liquid layer is excellent, so that the increase in the thermal resistance of the thermally conductive sheet is suppressed.

[0162] (Liquid thermally conductive material containing metal components)

[0163] The liquid thermally conductive material containing a metal component refers to a thermally conductive material containing a metal component that is liquid at a temperature of at least a portion of 0° C. to 50° C. The thermal conductivity of the liquid thermally conductive material containing a metal component is preferably 5 W / (m·K) or more, more preferably 10 W / (m·K) or more, and further preferably 30 W / (m·K) or more.

[0164] The liquid heat-conductive material containing a metal component may be a material consisting of a liquid metal component, or may be a material consisting of a liquid metal component and other components.

[0165] The content of the metal component in the liquid thermally conductive material may be 50% to 100% by mass, 70% to 100% by mass, or 90% to 100% by mass relative to the total amount of the liquid thermally conductive material.

[0166] The melting point of the metal component is preferably 50°C or lower, more preferably 45°C or lower, and further preferably 0°C to 40°C.

[0167] Examples of the metal component include gallium, indium, and tin, among which a metal component containing gallium is preferred.

[0168] 〔Thermal Conductive Sheet〕

[0169] The thermally conductive sheet of the present disclosure comprises: a thermally conductive layer, the thermally conductive layer containing a thermally conductive material containing thermally conductive particles; and a liquid layer, the liquid layer being located on at least a portion of the main surface of the thermally conductive layer and containing a first liquid thermally conductive material or a second liquid thermally conductive material, the first liquid thermally conductive material being the liquid thermally conductive material of the present disclosure, and the second liquid thermally conductive material being a liquid thermally conductive material containing a metal component.

[0170] The preferred embodiment of the first liquid heat-conducting material is the same as the preferred embodiment of the liquid heat-conducting material described above. The preferred embodiment of the second liquid heat-conducting material is the same as the liquid heat-conducting material containing a metal component in the combination 2 of components for making a heat-conducting sheet described above.

[0171] The surface of the thermally conductive sheet of the present invention that contacts the adherend sometimes has unevenness. In this case, most of the thermal resistance comes from the resistance (contact thermal resistance) caused by the gap generated by the contact between the thermally conductive sheet and the adherend such as the heating element and the heat sink that contacts the thermally conductive sheet. In the thermally conductive sheet of the present invention, a liquid layer containing the first liquid thermally conductive material or the second liquid thermally conductive material is arranged on at least a portion of the main surface of the thermally conductive layer, and the liquid layer flows due to heat, pressure, etc. when the thermally conductive sheet and the adherend such as the heating element and the heat sink are heated and pressed. The gap generated when the thermally conductive sheet and the adherend are heated and pressed (for example, the gap caused by the unevenness of the thermally conductive sheet) is filled by the liquid layer due to the flow of the liquid layer. As a result, the gap between the thermally conductive sheet and the adherend can be reduced, and the thermally conductive sheet and the adherend can be made to fit tightly, so that the contact thermal resistance is greatly reduced.

[0172] Contact thermal resistance is also likely to occur when there are irregularities on the surface of an adherend such as a heating element or a heat sink. In this case, it is difficult to reduce the thermal resistance by adjusting the orientation of the thermally conductive filler contained in the thermally conductive sheet. On the other hand, by using the thermally conductive sheet disclosed herein, the thermally conductive sheet and the adherend with irregularities on the surface can be closely fitted with the aid of a liquid layer. At this time, the gap generated when the thermally conductive sheet and the adherend are heated and pressed (for example, the gap caused by the irregularities of the adherend) is filled with the liquid layer, so the contact thermal resistance is greatly reduced.

[0173] The average thickness of the heat-conducting layer is not particularly limited and can be appropriately selected according to the purpose. The thickness of the heat-conducting layer can be appropriately selected according to the specifications of the semiconductor package used. The smaller the thickness, the lower the thermal resistance tends to be, and the larger the thickness, the higher the warpage tracking property tends to be. The average thickness of the heat-conducting layer can be 20 μm to 3000 μm, preferably 30 μm to 500 μm, and more preferably 50 to 400 μm from the viewpoint of thermal conductivity and adhesion.

[0174] The average thickness of the heat conductive layer is obtained by observing the cross section of the object to be measured using an electron microscope, measuring the thickness at three random locations, and calculating the arithmetic average thereof.

[0175] In the thermally conductive sheet disclosed herein, the liquid layer may be located on at least a portion of the main surface of the thermally conductive layer. The liquid layer may be located on the entire main surface, or on a portion of the main surface (e.g., a portion in contact with an adherend such as a heating element or a heat sink).

[0176] The liquid layer may be located on one main surface of the heat conducting layer, or the liquid layer may be located on two main surfaces of the heat conducting layer.

[0177] The maximum thickness of the liquid layer is preferably 0.5 μm to 50 μm, more preferably 0.5 μm to 30 μm, and even more preferably 0.5 μm to 20 μm. When the maximum thickness of the liquid layer is 0.5 μm or more, there is a tendency to further reduce the contact thermal resistance by further reducing the gap between the adherend and the thermally conductive sheet. When the maximum thickness of the liquid layer is 50 μm or less, the thermal conductivity of the thermally conductive sheet is more excellent, and there is a tendency to suppress the liquid layer from leaking to the outside when the adherend is in contact with the thermally conductive sheet.

[0178] The maximum thickness of the heat conductive layer and the maximum thickness of the liquid layer can be measured by observing the cross section of the measurement object using an electron microscope. Alternatively, the maximum thickness of the heat conductive layer can be measured using a micrometer, or the maximum thickness of the heat conductive layer and the maximum thickness of the heat conductive sheet having the liquid layer can be measured, and the maximum thickness of the liquid layer can be measured by subtracting the maximum thickness of the heat conductive layer from the maximum thickness of the heat conductive sheet.

[0179] When the liquid layers are formed on the two main surfaces of the heat conductive layer, the maximum thickness of the liquid layer refers to the maximum value of the sum of the thicknesses of the liquid layers formed on the two main surfaces.

[0180] When the liquid layer includes the first liquid thermally conductive material, the liquid layer may be curable or curable by heating. When curable by heating, for example, the first liquid thermally conductive material preferably includes the aforementioned thermosetting resin component that is liquid at 25°C.

[0181] The thermally conductive sheet may have a protective film on at least one surface, preferably on both surfaces, so that the pressure-sensitive adhesive surface of the thermally conductive sheet can be protected.

[0182] The protective film may be, for example, a resin film of polyethylene, polyester, polypropylene, polyethylene terephthalate, polyimide, polyetherimide, polyether naphthalate, methylpentene, etc.; coated paper, coated cloth, and metal foil of aluminum, etc. These protective films may be used alone or in combination of two or more to form a multilayer film. The protective film is preferably surface treated with a silicone-based, silica-based, or other release agent.

[0183] The use of the thermally conductive sheet is not particularly limited. When a semiconductor chip is used as a heating element and a heat sink is used as a heat sink, the thermally conductive sheet disclosed herein is particularly preferably used as a thermally conductive sheet (TIM1; Thermal Interface Material 1) between the semiconductor chip and the heat sink.

[0184] use Figure 1 Embodiments of the thermally conductive sheet will be described. The thermally conductive sheet of the present disclosure is not limited to the following embodiments.

[0185] Figure 1 The heat conducting sheet 1 shown includes a heat conducting layer 11 and liquid layers 12 and 13 . The liquid layer 12 is located on one main surface of the heat conducting layer 11 , and the liquid layer 13 is located on the other main surface of the heat conducting layer 11 .

[0186] like Figure 1 As shown, the unevenness can be reduced by providing liquid layers 12 and 13 on the two main surfaces of the thermally conductive sheet 1. By providing the liquid layers 12 and 13 on the main surface of the thermally conductive layer 11, the unevenness of the thermally conductive layer 11 can be filled with the liquid layers 12 and 13, and the unevenness of the surface of the adherend can also be filled with the liquid layers 12 and 13 when the thermally conductive sheet 1 is in contact with the adherend.

[0187] [Method for manufacturing thermal conductive sheet]

[0188] The method for manufacturing a thermally conductive sheet is not particularly limited as long as a thermally conductive sheet having the above-mentioned structure can be obtained. The method for manufacturing a thermally conductive sheet comprises: a step of preparing a composition containing the above-mentioned thermally conductive particles (also referred to as a "preparation step"); a step of forming the above-mentioned thermally conductive layer using the above-mentioned composition (also referred to as a "forming step"); and a step of forming a liquid layer on at least a portion of the main surface of the above-mentioned thermally conductive layer (also referred to as a "liquid layer forming step").

[0189] <Preparation process>

[0190] In the preparation step, a composition containing thermally conductive particles and any other components is prepared. As a method for blending the components, any method can be used without particular limitation as long as the components can be uniformly mixed.

[0191] <Formation process>

[0192] In the forming step, the thermally conductive layer is formed using a composition containing thermally conductive particles and any other components. For example, the thermally conductive layer may be formed by molding the composition into a sheet.

[0193] <Liquid layer forming process>

[0194] The liquid layer forming step may be any method without particular limitation as long as a liquid layer can be formed on at least a portion of the main surface of the thermally conductive layer. For example, the first liquid thermally conductive material or the second liquid thermally conductive material may be applied to at least a portion of the main surface of the thermally conductive layer.

[0195] In the method for producing a thermally conductive sheet, it is preferred to produce a thermally conductive sheet in which the thermally conductive particles are the above-mentioned graphite particles (A) from the viewpoint of high thermal conductivity of the thermally conductive sheet. Examples of the method for producing a thermally conductive sheet containing graphite particles (A) include the following method.

[0196] In one embodiment, a method for manufacturing a thermally conductive sheet comprises: a step of preparing a composition containing graphite particles (A) and any other components (the above-mentioned preparation step); a step of forming the above-mentioned composition into sheets to obtain a sheet (a part of the above-mentioned formation step, also referred to as a "sheet making step"); a step of making a stack of the above-mentioned sheets (a part of the above-mentioned formation step, also referred to as a "stack making step"); a step of slicing the side end surface of the above-mentioned stack (a part of the above-mentioned formation step, also referred to as a "slicing step"); and a step of forming a liquid layer on at least a part of the main surface of the sliced ​​sheet (equivalent to the thermally conductive layer) obtained by slicing (the above-mentioned liquid layer forming step).

[0197] Furthermore, the method for producing a thermally conductive sheet may further include a step of attaching and laminating a protective film on the thermally conductive sheet after the liquid layer forming step (also referred to as a "lamination step").

[0198] By manufacturing a thermally conductive sheet using this method, an efficient thermal conduction path can be easily formed, so there is a tendency that a thermally conductive sheet having high thermal conductivity and excellent adhesion can be obtained.

[0199] <Preparation process>

[0200] In the preparation step, a composition containing graphite particles (A) and any other components (e.g., component (B) that is liquid at 25°C, acrylate polymer (C), hot melt agent (D), antioxidant (E), and other components) is prepared. As a method for mixing the components, any method can be used without particular limitation as long as the components can be uniformly mixed. In addition, the composition can also be prepared by purchasing commercially available substances. For details of the preparation of the composition, reference can be made to paragraph

[0033] of Japanese Patent Publication No. 2008-280496.

[0201] <Sheet production process>

[0202] The sheet making process can be carried out by any method without particular limitation as long as the composition obtained in the previous process can be sheeted. For example, it is preferably implemented by at least one forming method selected from rolling, pressing, extrusion, and coating. The details of the sheet making process can refer to paragraph

[0034] of Japanese Patent Publication No. 2008-280496.

[0203] <Laminate production process>

[0204] The laminate production step forms a laminate of the sheets obtained in the previous steps. The laminate can be produced, for example, by stacking a plurality of independent sheets in sequence, or by folding a single sheet, or by rolling a single sheet. For details of the laminate production step, reference can be made to paragraphs

[0035] to

[0037] of Japanese Patent Application Publication No. 2008-280496.

[0205] <Slicing process>

[0206] The slicing step may be any method as long as the side end surface of the laminate obtained in the previous step can be sliced, and there is no particular limitation. From the viewpoint of forming an extremely effective heat conduction path using the graphite particles (A) that penetrate the thickness direction of the heat conductive layer and further improving the thermal conductivity, it is preferred to slice at a thickness of less than 2 times the mass average particle size of the graphite particles (A). For details of the slicing step, reference can be made to paragraph

[0038] of Japanese Patent Publication No. 2008-280496.

[0207] <Liquid layer forming process>

[0208] The liquid layer forming step may be any method without particular limitation as long as it can form a liquid layer on at least a portion of the main surface of the sliced ​​sheet (equivalent to the thermally conductive layer) obtained by slicing. For example, the first liquid thermally conductive material or the second liquid thermally conductive material may be applied to at least a portion of the main surface of the thermally conductive layer.

[0209] <Lamination process>

[0210] The lamination step may be any method as long as the thermally conductive sheet obtained in the liquid layer forming step can be attached to the protective film, and is not particularly limited.

[0211] 〔Heat dissipation device〕

[0212] The heat dissipation device disclosed in the present invention is a device having a heating element, a heat dissipation element, and a heat conductive sheet of the present invention disposed between the heating element and the heat dissipation element, wherein the liquid layer is located on at least a portion of at least one of the main surfaces of the heat conductive layer located on the heating element side and the main surface located on the heat dissipation element side. Preferably, the liquid layer is located on at least a portion of the main surface of the heat conductive layer located on the heating element side and on at least a portion of the main surface of the heat dissipation element side, respectively, and more preferably, the liquid layer is located on a region of the main surface located on the heating element side that is opposite to the heating element and a region of the main surface located on the heat dissipation element side that is opposite to the heat dissipation element, respectively.

[0213] Examples of the heat generating body include semiconductor chips, semiconductor packages, power modules, etc. Examples of the heat dissipating body include radiators, heat sinks, water cooling pipes, etc.

[0214] Below, use Figure 2 An example of a heat dissipation device is described in more detail. A heat dissipation device using a semiconductor chip as a heating element and a heat sink as a heat sink is described. A semiconductor chip and a heat sink are examples of a heating element and a heat sink, respectively, and the present disclosure is not limited to them. One surface of a thermal conductive sheet 1 is made to fit tightly with a semiconductor chip 2, and the other surface of the thermal conductive sheet 1 is made to fit tightly with a heat sink 3. The semiconductor chip 2 is fixed to a substrate 4 using an underfill 5, and the heat sink 3 is fixed to the substrate 4 using a sealing material 6, and the fit between the thermal conductive sheet 1 and the semiconductor chip 2 and the heat sink 3 is improved by pressing. In addition, it is not necessary that there is one heating element and one heat sink for each thermal conductive sheet 1. For example, a plurality of semiconductor chips 2 may be provided for a single thermal conductive sheet 1, a single semiconductor chip 2 may be provided for a plurality of thermal conductive sheets 1, or a plurality of semiconductor chips 2 may be provided for a plurality of thermal conductive sheets 1. The liquid layer is located on the main surface of the thermal conductive sheet 1 on the semiconductor chip 2 side and on the main surface of the thermal conductive sheet 1 on the heat sink 3 side. For example, Figure 1 In the thermally conductive sheet 1 shown, the liquid layer 13 is located on the main surface of the thermally conductive sheet 1 on the semiconductor chip 2 side, and the liquid layer 12 is located on the main surface of the thermally conductive sheet 1 on the heat sink 3 side. Furthermore, the liquid layer 13 may be in contact with the semiconductor chip 2, and the liquid layer 12 may be in contact with the heat sink 3.

[0215] The heat sink is formed by disposing the heat conductive sheet of the present disclosure between the heating element and the heat sink. By stacking the heating element and the heat sink with the heat conductive sheet interposed therebetween, the heat generated by the heating element can be effectively transferred to the heat sink. By effectively conducting heat, a heat sink can be provided that has a longer service life and functions stably even in long-term use.

[0216] The temperature range in which the thermally conductive sheet can be appropriately used may be, for example, -10°C to 150°C, -10°C to 100°C, or -10°C to 80°C. Therefore, as the heat generating element, for example, semiconductor packages, displays, LEDs, electric lights, automotive power modules, and industrial power modules can be cited as examples of preferred heat generating elements.

[0217] Examples of heat sinks include heat sinks using aluminum or copper fins, plates, etc., aluminum or copper blocks connected to heat pipes, aluminum or copper blocks that circulate cooling liquid inside using a pump, and Peltier elements and aluminum or copper blocks having the same.

[0218] The heat dissipation device is formed by bringing the surfaces of the heat conductive sheet into contact with the heating element and the heat dissipating element. The method of bringing the heating element into contact with one surface of the heat conductive sheet and the method of bringing the heat dissipating element into contact with the other surface of the heat conductive sheet are not particularly limited as long as they can be fixed in a sufficiently close state.

[0219] For example, a heat-conducting sheet is arranged between the heating element and the heat-dissipating element, and is fixed by a clamp that can be pressurized to about 0.05MPa to 1MPa, and the heating element is heated in this state, or a method of heating to about 80°C to 200°C by using an oven or the like can be cited. In addition, a method of using a pressing machine that can be heated and pressurized at 80°C to 200°C and 0.05MPa to 1MPa can be cited. In this method, the preferred pressure range is 0.10MPa to 1MPa, and the preferred temperature range is 100°C to 180°C. By setting the pressure to more than 0.10MPa or setting the heating temperature to more than 100°C, there is a tendency to obtain excellent adhesion. In addition, by making the pressure less than 1MPa or the heating temperature less than 180°C, there is a tendency to further improve the reliability of the close fit. It can be considered that this is because the heat-conducting sheet can be prevented from being excessively compressed and thinning the thickness, or the strain or residual stress of the surrounding parts can be prevented from becoming too large.

[0220] The heat conductive sheet disposed between the heating element and the heat dissipating element is not particularly limited as long as it is the above-mentioned heat conductive sheet. Figure 1 The heat conductive sheet shown is arranged between the heating element and the heat dissipating element.

[0221] use Figure 1 In the case of the heat conductive sheet 1 shown, by heating and pressing the heat conductive sheet 1 between the heat generating body and the heat dissipating body, the liquid layers 12 and 13 on the main surface of the heat conductive sheet 1 flow. The gap generated when the heat conductive sheet 1, the heat generating body and the heat dissipating body are heat-pressed is filled by the flowing liquid layer. Thus, the gap between the heat conductive sheet and the adherend can be reduced.

[0222] For example, when the first liquid heat-conducting material containing a thermosetting resin component is used so that the liquid layer can be cured by heating, when the liquid layer flows to fill the gap between the heat-conducting sheet and the adherend by heat-compression bonding, the thermosetting resin component is cured by heating. Thus, the heat-conducting sheet and the adherend can be closely attached to each other by means of the adhesive layer formed by curing the liquid layer.

[0223] The ratio (compression rate) of the reduced thickness of the thermally conductive sheet after pressure bonding to the initial thickness before being arranged between the heat generating element and the heat dissipating element and pressure bonded may be 1% to 35%.

[0224] Fixation may be performed using a clamp such as a screw or a spring in addition to a clip, and further fixing by a commonly used means such as an adhesive is preferred from the viewpoint of maintaining close contact.

[0225] At the interface between the heating element and the heat conducting sheet and at the interface between the heat sink and the heat conducting sheet, the porosity calculated as the ratio of the area of ​​the gas region to the area of ​​the measurement region is preferably 0% to 20.0%, and more preferably 0% to 15.0%. As a result, the gaps generated when the heat conducting sheet and the heating element or the heat sink are heated and pressed (for example, the gaps from the unevenness of the heat conducting sheet and the gaps from the unevenness of the heating element or the heat sink) are reduced. As a result, it is inferred that the contact thermal resistance is greatly reduced.

[0226] In the present disclosure, it is preferred that the porosity on both the main surface side of the heat conductive layer where the liquid heat conductive material is present and the main surface side of the heat conductive layer where the liquid heat conductive material is not present satisfy the above numerical range.

[0227] In the present disclosure, the porosity of the interface can be calculated as follows. First, an ultrasonic imaging diagnostic device (e.g., Insight-300, Insight KK) is used to observe the adhesion state of the interface by reflection method at 35 MHz. The ratio of the area of ​​the gas region without adhesion is calculated, and the porosity of the interface can be calculated based on the following formula.

[0228] Interface porosity (%) = 100 × (area of ​​gas region / area of ​​measurement region)

[0229] The numerical range of the porosity of the interface can be adjusted by, for example, adjusting the viscosity of the liquid thermally conductive material at 25° C., the amount of the liquid thermally conductive material applied to the thermally conductive layer, the compressibility of the thermally conductive sheet, and the like.

[0230] [Example]

[0231] Hereinafter, the present invention will be described in detail by way of examples, but the present invention is not limited to these examples.

[0232] [Example 1 to Example 4]

[0233] The following materials were charged into a kneader (MORIYA MA CORPORATION, DS3-SGHM-E type pressurized double-arm kneader) at the mixing ratio (volume %) shown in Table 1, and kneaded at a temperature of 150° C. to obtain a composition.

[0234] <Graphite particles (A)>

[0235] (A)-1: scaly expanded graphite particles (Showa Denko Materials Co., Ltd. "HGF-L", mass average particle size: 270 μm, confirmed by the aforementioned method using X-ray diffraction measurement that the six-membered ring planes in the crystal are oriented along the plane direction of the scaly particles).

[0236] <Liquid component (B)>

[0237] (B)-1: isobutylene-n-butene copolymer (NOF Corporation "NOF Polybutene TM EMAWET (registered trademark), grade 30N)

[0238] (B)-2: Homopolymer of isobutylene ("Tetrax 6T" produced by Nippon Oil Corporation)

[0239] <Acrylate polymer (C)>

[0240] (C)-1: Acrylate copolymer resin (butyl acrylate / ethyl acrylate / acrylonitrile / acrylic acid copolymer, weight average molecular weight: 530,000, Tg = -39°C)

[0241] <Hot melt (D)>

[0242] (D)-1: Hydrogenated petroleum resin (Arakawa Chemical Industries, Ltd. "Arkon P90")

[0243] <Antioxidant (E)>

[0244] (E)-1: Hindered phenol antioxidant (ADK STAB AO-60 from ADEKA Corporation)

[0245] (Fabrication of thermal conductive layer)

[0246] The kneaded composition is placed in an extrusion molding machine (Parker Co., Ltd., trade name: HKS 40-15 extruder), extruded into a flat plate shape with a width of 20 cm and a thickness of 1.5 mm to 1.6 mm to obtain a primary sheet. The obtained primary sheet is pressed and punched with a 40 mm × 150 mm die blade, 61 punched sheets are stacked, and a spacer with a height of 80 mm is clamped in a manner of 80 mm. Pressure is applied to the stacking direction at 90°C for 30 minutes to obtain a 40 mm × 150 mm × 80 mm stack. Next, the 80 mm × 150 mm side end surface of the stack is sliced ​​with a woodworking slicer to obtain a thermal conductive layer with a thickness of 0.11 mm. It should be noted that the thickness of the thermal conductive layer used in each embodiment and each comparative example is of the same degree.

[0247] (Manufacturing of thermal conductive sheet)

[0248] A liquid thermally conductive material having the composition shown below is prepared. The prepared liquid thermally conductive material is applied to one or two main surfaces of the thermally conductive layer obtained as described above, and the liquid component is evenly spread with a special spatula to obtain a thermally conductive sheet having a liquid layer formed on one or two main surfaces of the thermally conductive layer.

[0249] <Composition of liquid thermal conductive material>

[0250] First liquid thermally conductive material (liquid material 1 in the table): AS-05A from Artic Silver Inc. (containing a liquid ester compound and silver particles, a filler content of 86% by mass, a viscosity of 145 Pa·s at 25° C., and a thermal conductivity of 9 W / (m·K))

[0251] Second liquid thermally conductive material (liquid material 2 in the table): JP-DX1 from JunPus International Co., Ltd. (containing a liquid organic silicon compound and nanodiamonds, a filler content of 92% by mass, a viscosity of 3000 Pa·s at 25°C, and a thermal conductivity of 16 W / (m·K))

[0252] Third liquid thermal conductive material (liquid material 3 in the table): Conductonaut from Thermal Grizzly (metal containing tin, gallium, and indium, viscosity at 25°C is 0.0021 Pa·s, thermal conductivity is 73 W / (m·K))

[0253] (Comparative Example 1 and Comparative Example 2)

[0254] The materials shown in Table 1 were mixed, laminated, pressed, and sliced ​​in the same steps as in Examples 1 to 4 at the mixing ratios (volume %) shown in Table 1 to prepare a thermally conductive layer. In Comparative Example 1, a liquid layer was not formed, and the thermally conductive layer was used as a thermally conductive sheet. In Comparative Example 2, a thermally conductive sheet having a liquid layer was obtained in the same manner as in each Example except that a grease having a thermal conductivity of less than 5 W / (m·K) shown below was used.

[0255] Liquid material (liquid material 4 in the table): G-747 from Shin-Etsu Chemical Co., Ltd. (containing a liquid organic silicon compound and zinc oxide, a filler content of 84% by mass, a viscosity of 50 Pa·s at 25°C, and a thermal conductivity of 0.9 W / (m·K))

[0256] Table 1

[0257]

[0258] The thermally conductive sheets of Examples 1 to 4 and Comparative Examples 1 and 2 were evaluated by the following methods. The results are shown in Tables 2 and Figure 3 middle.

[0259] (Determination of thermal resistance)

[0260] Thermal resistance was measured using a desktop xenon flash analyzer (LFA 467Hyper Flash). A Φ14mm thermally conductive sheet was sandwiched between 1mm copper plates to produce a three-layer structure sample. As sample preparation conditions, the temperature was 150°C and the pressure was 0.14MPa for 3 minutes, and then fully cooled at room temperature. In addition, as a pretreatment for the measurement, the copper surface was blackened with carbon spray, and then the measurement was performed. The thermal conductivity λ after removing the influence of the copper plate part from the three-layer structure was obtained. Based on the obtained thermal conductivity λ and thickness t, the thermal conductivity per unit area (1cm 2 ) thermal resistance value X(K·cm 2 / W).

[0261] X=(10×t) / λ

[0262] t: Thickness of the thermally conductive sheet of Examples 1 to 4 or Comparative Examples 1 to 2 (mm)

[0263] λ: Thermal conductivity (W / m·K)

[0264] (Evaluation of interface porosity)

[0265] For the sample of the three-layer structure prepared according to the method described in (Determination of thermal resistance), the porosity of the interface was evaluated as follows. Using an ultrasonic imaging diagnostic device (Insight-300, Insight KK), the adhesion state of the interface was observed by the reflection method at 35 MHz, a gain level of 10 dB, and a contrast threshold of 30% to 70%. Furthermore, the image was binarized using image analysis software (Image J) (specifically, the histogram of 0 to 83 was used as the black part and 84 to 255 was used as the white part for black and white conversion), and the area of ​​Φ11 mm (the area of ​​the measurement area, it should be noted that) was calculated. Figure 3 The porosity (%) of the interface was calculated based on the following formula: The porosity was not measured in Example 3.

[0266] Interface porosity (%) = 100 × (area of ​​gas region / area of ​​measurement region)

[0267] (Thickness Evaluation)

[0268] The thermally conductive sheets of Examples 1 to 4 and Comparative Example 1 were compressed under the same conditions. Next, the maximum thickness of the thermally conductive sheet after compression ("thickness after compression" in Table 2) was measured using a micrometer. The maximum thickness of the liquid layer was obtained by subtracting the maximum thickness of the thermally conductive sheet having a liquid layer from the maximum thickness of the thermally conductive sheet without a liquid layer.

[0269] Table 2

[0270]

[0271] It was confirmed that Examples 1 to 4 using a liquid material having a thermal conductivity of 5 W / (m·K) or more can reduce thermal resistance compared to Comparative Example 1 using no liquid material and Comparative Example 2 using a liquid material having a thermal conductivity of less than 5 W / (m·K).

[0272] The disclosure of PCT / JP2022 / 028528 is incorporated in its entirety into this specification by reference.

[0273] All documents, patent applications, and technical standards described in this specification are incorporated by reference into this specification to the same extent as if each individual document, patent application, and technical standard was specifically and individually described as being incorporated by reference.

Claims

1. A liquid thermally conductive material having a thermal conductivity of 5 W / (m·k) or more, which is applied to at least a portion of a thermally conductive layer containing thermally conductive particles to form a liquid layer. 2 . The liquid thermally conductive material according to claim 1 , comprising a thermally conductive filler and a resin component.

3. The liquid thermally conductive material according to claim 2, wherein: The particle size of the thermally conductive filler is 0.1 μm to 50 μm.

4. The liquid thermally conductive material according to claim 2 or claim 3, wherein: The resin component includes a thermosetting resin component. 5 . The liquid thermally conductive material according to claim 1 , which has a viscosity of 4000 Pa·s or less at 25° C. 6 . A combination of components for producing a thermally conductive sheet, comprising the liquid thermally conductive material according to claim 1 , and a thermally conductive material containing thermally conductive particles.

7. A combination of components for producing a thermally conductive sheet, comprising a liquid thermally conductive material containing a metal component and a thermally conductive material containing thermally conductive particles.

8. The combination of components for making a thermally conductive sheet according to claim 7, wherein: The melting point of the metal component is 50° C. or lower.

9. A thermally conductive sheet comprising: a heat-conductive layer comprising a heat-conductive material including heat-conductive particles; and A liquid layer, wherein the liquid layer is located on at least a portion of the main surface of the thermally conductive layer and comprises a first liquid thermally conductive material or a second liquid thermally conductive material, wherein the first liquid thermally conductive material is the liquid thermally conductive material according to any one of claims 1 to 5, and the second liquid thermally conductive material is a liquid thermally conductive material comprising a metal component.

10. The thermally conductive sheet according to claim 9, wherein: The thermally conductive particles include at least one type of graphite particles (A) selected from flaky particles, ellipsoidal particles, and rod-shaped particles. For the thermally conductive layer, in the case of the flaky particles, the surface direction is oriented along the thickness direction of the thermally conductive layer, in the case of the ellipsoidal particles, the major axis direction is oriented along the thickness direction of the thermally conductive layer, and in the case of the rod-shaped particles, the major axis direction is oriented along the thickness direction of the thermally conductive layer.

11. The thermally conductive sheet according to claim 9 or claim 10, wherein: The maximum thickness of the liquid layer is 0.5 μm to 20 μm.

12. The thermally conductive sheet according to any one of claims 9 to 11, wherein The liquid layer contains the first liquid thermally conductive material, and the liquid layer can be solidified by heating.

13. A heat dissipation device comprising a heating element, a heat dissipation element, and a heat conductive sheet according to any one of claims 9 to 11 disposed between the heating element and the heat dissipation element, in, The liquid layer is located on at least a portion of at least one of a main surface of the heat conductive layer located on the heat generating element side and a main surface of the heat radiating element side.

14. A heat dissipation device comprising a heating element, a heat dissipation element, and a heat conductive sheet, wherein the heat conductive sheet is arranged between the heating element and the heat dissipation element and is the heat conductive sheet according to claim 12, and the heat conductive sheet comprises an adhesive layer formed by solidifying the liquid layer. in, The adhesive layer is located on at least a portion of at least one of a main surface of the heat conductive layer located on the heating element side and a main surface of the heat conductive layer located on the heat radiating element side.

15. A method for manufacturing a thermally conductive sheet, the method comprising manufacturing the thermally conductive sheet according to any one of claims 9 to 12, The manufacturing method of the thermal conductive sheet comprises: A step of preparing a composition containing the thermally conductive particles; A process of forming the thermal conductive layer using the composition; and A step of forming a liquid layer on at least a portion of the main surface of the heat conductive layer.

16. A method for manufacturing a thermally conductive sheet, which is a method for manufacturing the thermally conductive sheet according to claim 10, The manufacturing method of the thermal conductive sheet comprises: A step of preparing a composition containing the graphite particles (A); A step of forming the composition into a sheet to obtain a sheet; a step of manufacturing a laminate of the sheet material; A step of slicing the side end surface of the laminate; as well as A step of forming a liquid layer on at least a portion of the main surface of the sliced ​​sheet corresponding to the heat conductive layer obtained by slicing.

Citation Information

Patent Citations

  • Heat conductive material and manufacturing method thereof

    JP2001250894A

  • Heat conducting sheet and its manufacturing method

    JP2002026202A

  • Heat-conductive sheet, method for producing the same, and heat radiator using the same

    JP2008280496A